1987
DOI: 10.1007/bf01312463
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and pharmacokinetics of 5-aminosalicylic acid

Abstract: There is accumulating clinical evidence that 5-aminosalicylic acid (5-ASA), a primary metabolite of sulfasalazine (SAS), represents the therapeutic active moiety of the azo-compound SAS in the treatment of chronic inflammatory bowel disease (IBD). Since it is presumed that 5-ASA acts from the lumen of the intestine, it is important to know how much 5-ASA is released from its special galenic formulations. After liberation of 5-ASA in the terminal ileum (only slow release oral preparations of 5-ASA) and colon (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
2

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 17 publications
2
35
1
2
Order By: Relevance
“…On the other hand, the percentage of 5-ASA and Ac-5-ASA excreted into the urine after the administration of the enema was approximately 0.3% and 11%, respectively. These results differed from the clinical findings reported by Klotz and Maier, 13) who demonstrated that about one-third of the dose of 5-ASA is recovered in the urine, almost entirely as Ac-5-ASA. The reason for discrepancy between their results and ours remains to be elucidated, although it might be due to differences in pharmacokinetic behavior between healthy volunteers and patients with inflammatory bowel disease and/or the genetic polymorphism of N-acetyltransferase.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…On the other hand, the percentage of 5-ASA and Ac-5-ASA excreted into the urine after the administration of the enema was approximately 0.3% and 11%, respectively. These results differed from the clinical findings reported by Klotz and Maier, 13) who demonstrated that about one-third of the dose of 5-ASA is recovered in the urine, almost entirely as Ac-5-ASA. The reason for discrepancy between their results and ours remains to be elucidated, although it might be due to differences in pharmacokinetic behavior between healthy volunteers and patients with inflammatory bowel disease and/or the genetic polymorphism of N-acetyltransferase.…”
Section: Resultscontrasting
confidence: 57%
“…However, clinical pharmacokinetic studies of 5-ASA in the enema form have been limited in Japan, although there have been several studies abroad on the pharmacokinetics and bioavailability of SASP and 5-ASA preparations. [12][13][14] On the other hand, it is well known that genetic polymorphism occurs in N-acetyltransferase: the frequency of the poor metabolizer with deficient activity is about 50% in Caucasians and 10% in Japanese. This genetic polymorphism might lead to differences in the pharmacokinetics of SASP and 5-ASA between Caucasians and Japanese.…”
mentioning
confidence: 99%
“…Pharmacokinetic parameters of mesalazine observed here are similar to those reported, including saturation of acetylation for chronic administration [1,18]. Because of the short elimination half-life of mesalazine of clearly less than 3 hours [1,7], a prolonged release preparation is needed for maintaining plasma concentrations during a dosing interval, but also for direct delivery to any intestinal site of action.…”
Section: Discussionsupporting
confidence: 60%
“…Because of the short elimination half-life of mesalazine of clearly less than 3 hours [1,7], a prolonged release preparation is needed for maintaining plasma concentrations during a dosing interval, but also for direct delivery to any intestinal site of action. Mesalazine release from this formulation has been reported to occur throughout the gastrointestinal tract [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation